2015
DOI: 10.1111/jpn.12286
|View full text |Cite
|
Sign up to set email alerts
|

Dose–responses of zinc–methionine supplements on growth, blood metabolites and gastrointestinal development in sheep

Abstract: The effects of zinc-methionine (Zn-Met) supplementation on growth, blood metabolites and gastrointestinal development were investigated in two experiments with sheep. The objective of Experiment 1 was to determine the effects of Zn-Met supplementation on hormones and metabolites involved in growth and energy balance regulation, while Experiment 2 aimed to determine the effects of Zn-Met on feed intake, body weight, gastrointestinal development and liver glycogen concentration in lamb. The animals were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
2
8
2
1
Order By: Relevance
“…However, no effect on performance, feed intake or tissue zinc concentration of sheep fed with diets exceeding the requirements of ruminants was observed (Henry, Littell, & Ammerman, ; Wrightt & Spears, ). Data on the gastrointestinal histomorphology of the animals showed that Zn‐methionine supplementation (concentrations of 0.4, 0.8 and 1.2 g/day) is beneficial for promoting gastrointestinal tract growth in growing lambs (Jafarpour, Khorvash, Rahmani, Pezeshki, & Hosseini Ghaffari, ). The energetic efficiency of growing ruminants is higher if starch is digested in the small intestine rather than the rumen (Owens, Zinn, & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no effect on performance, feed intake or tissue zinc concentration of sheep fed with diets exceeding the requirements of ruminants was observed (Henry, Littell, & Ammerman, ; Wrightt & Spears, ). Data on the gastrointestinal histomorphology of the animals showed that Zn‐methionine supplementation (concentrations of 0.4, 0.8 and 1.2 g/day) is beneficial for promoting gastrointestinal tract growth in growing lambs (Jafarpour, Khorvash, Rahmani, Pezeshki, & Hosseini Ghaffari, ). The energetic efficiency of growing ruminants is higher if starch is digested in the small intestine rather than the rumen (Owens, Zinn, & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…Current dietary Zn recommendations in sheep range from 20 to 51 mg/kg dependent on physiological status of the animal, while recommendations in cattle are less defined, at 30 mg/kg independent of physiological state of the animal (NRC, 2007(NRC, , 2015. Appropriate concentrations of dietary Zn have shown to be beneficial in several economic aspects of sheep production, including but not limited to growth, reproduction, and wool characteristics (Underwood and Somers, 1969;White et al, 1994;Jafarpour et al, 2015).…”
Section: Dicussionmentioning
confidence: 99%
“…These studies demonstrated better bioavailability of organic forms (bioplexes), socalled chelates, i.e., compounds of metal ions and the ligand (protein or amino acid). They do not demonstrate any antagonisms and interactions that can occur between inorganic salts and other components like hydroxides, phosphates, carbonates and oxygen, which ensures highest bioavailability of organic forms (Hosnedlova et al, 2007;Kinal and Slupczynska, 2011;Sahoo et al, 2014). The chelates also retain stability at varying pH levels in the digestive tract (Hassan et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The advantage of inorganic forms is their low cost; however, it is generally believed that this form is less bioavailable compared to the organic one. Many authors compared in their research the bioavailability of inorganic and organic forms of zinc in the nutrition of animals, especially ruminants (Spears, 1989;Rojas et al, 1995;Cao et al, 2000;Ryan et al, 2002;Pal et al, 2010;Hassan et al, 2011;Jafarpour et al, 2015;Page et al, 2017). These studies demonstrated better bioavailability of organic forms (bioplexes), socalled chelates, i.e., compounds of metal ions and the ligand (protein or amino acid).…”
Section: Introductionmentioning
confidence: 99%